17β-Estradiol Regulates Microglia Activation and Polarization in the Hippocampus Following Global Cerebral Ischemia. (18th April 2018) - Thakkar, Roshni; Wang, Ruimin; Wang, Jing; Vadlamudi, Ratna K.; Brann, Darrell W.
Abstract : 17 β -Estradiol (E2) is a well-known neuroprotective hormone, but its role in regulation of neuroinflammation is less understood. Recently, our lab demonstrated that E2 could regulate the NLRP3 (NOD-like receptor protein 3) inflammasome pathway in the hippocampus following global cerebral ischemia (GCI). Here, we examined the ability of E2 to regulate activation and polarization of microglia phenotype in the hippocampus after global cerebral ischemia (GCI). Our in vivo study in young adult ovariectomized rats showed that exogenous low-dose E2 profoundly suppressed microglia activation and quantitatively shifted microglia from their "activated, " amoeboid morphology to a "resting, " ramified morphology after GCI. Further studies using M1 "proinflammatory" and M2 "anti-inflammatory" phenotype markers showed that E2 robustly suppressed the "proinflammatory" M1 phenotype, while enhancing the "anti-inflammatory" M2 microglia phenotype in the hippocampus after GCI. These effects of E2 may be mediated directly upon microglia, as E2 suppressed the M1 while enhancing the M2 microglia phenotype in LPS- (lipopolysaccharide-) activated BV2 microglia cells in vitro . E2 also correspondingly suppressed proinflammatory while enhancing anti-inflammatory cytokine gene expression in the LPS-treated BV2 microglia cells. Finally, E2 treatment abolished the LPS-induced neurotoxic effects of BV2 microglia cells upon hippocampal HT-22 neurons. Collectively, our study findings suggest a novel E2-mediated neuroprotective effect via regulation of microglia activation and promotion of the M2 "anti-inflammatory" phenotype in the brain.